استفادة الإنستجرام كوسيلة تعليمية في تعلم المفردات لدى طلاب الصف الثامن بالمدرسة الإسلامية بيضاء الأحكام بيريوك مدينة تانجيرانج - Nurhasanah, Irma; Nasrullah; Moh. Aman (INTIFA: Journal of Education and Language, 2024)
ABSTRACTArabic language learning in schools is often perceived as difficult and less engaging by students. One of the main reasons for this is the limited use of innovative instructional media that align with the advancements of the times. In today’s digital era, social media presents a promising opportunity that can be leveraged as an effective and engaging educational tool. Among the most popular platforms among students is Instagram. Accordingly, this study focuses on Arabic language education, particularly in the area of vocabulary acquisition (mufradat), with the aim of exploring how Instagram can be utilized to support the learning process of eighth-grade students at SMP Islam Baidhaul Ahkam in Tangerang City. It also seeks to identify Instagram’s features that contribute to increasing student engagement and improving learning outcomes.This research adopts a qualitative descriptive approach, employing data collection techniques such as observation, interviews, documentation, and tests using the polling feature in Instagram Stories. The findings reveal that students showed greater interest and became more actively involved in the learning process. The average student score increased from 33.63% to 90.91% after using Instagram as a learning medium. Furthermore, features such as feed posts, short videos (reels), and stories proved to be effective in delivering content visually and attractively. ملخّص البحثيعد تعليم اللغة العربية في المدارس غالبا صعب الفهم وقليل الجاذبية بالنسبة للطلاب، ومن أبرز أسبابه قلة استخدام الوسائل التعليمية المبتكرة التي تواكب تطور العصر. وفي هذا العصر الرقمي، أصبحت وسائل التواصل الاجتماعي فرصة واعدة يمكن استغلالها كوسيلة تعليمية فعالة وجذابة. وتعد منصة إنستجرام من أشهر هذه الوسائل لدى فئة الطلاب. لذلك، يركز هذا البحث على تعليم اللغة العربية، وبشكل خاص على جانب المفردات، بهدف معرفة كيفية توظيف إنستجرام لدعم عملية التعلم لدى طلاب الصف الثامن في المدرسة الإسلامية بيضاء الأحكام بمدينة تانجيرانج، بالإضافة إلى تحديد الخصائص التي تسهم في تعزيز الاهتمام والنتائج التعليمية. يعتمد هذا البحث على المنهج الوصفي النوعي، باستخدام تقنيات الملاحظة، والمقابلة، والتوثيق، والاختبار من خلال خاصية الاستطلاع (Polling) في قصص إنستجرام. وقد أظهرت نتائج البحث أن الطلاب أصبحوا أكثر اهتماما وتفاعلا خلال عملية التعلم. وقد ارتفع متوسط درجات الطلاب من ‎%33.63 إلى ‎%90.91 بعد استخدام إنستجرام كوسيلة تعليمية. كما تبين أن خصائص النشر (Feed)، والمقاطع القصيرة (Reels)، والقصص (Stories) فعالة في تقديم المحتوى بشكل بصري وجذاب.